Modeling the Thermal Behavior of Permanent Magnet Synchronous Motors - Lotfi, Abdelhakim; Marcsa, Dániel; Horváth, Zoltán (International Journal of Engineering and Management Sciences, 2019)
The aim of this study is to present a thermal analysis of a permanent magnet synchronous machine based on finite element method. The developed model can be used to predict temperature distribution inside the studied motor during the rated operation. Electromagnetic computation is carried out with the aid of two 2D finite-element (FE) simulations on the cross-section of the PM motor. To analyse the process of heat transfer in an electrical machine, empirical correlations are used to describe the convective heat transfer from the different surfaces of the PM motor. The heat transfer coefficient is determined using dimensionless numbers and Nusselt number. After the loss calculation, the temperatures of the machine are calculated by using 3D finite element method. The results obtained by the model are compared with experimental results from testing the prototype electric motor.